2003
DOI: 10.1620/tjem.201.201
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Lactate and Pyruvate Concentrations after Taking a Bath in Hot Deep Seawater

Abstract: The use of deep seawater (DSW) in thalassotherapy has begun in Japan. To clarify the health effects of DSW on the human body, we investigated the changes in plasma lactate and pyruvate concentrations, or subjective judgment scores, after bathing at rest in 9 healthy young men. Subjects were immersed for 10 minutes in DSW, surface seawater (SSW), and tap water (TW) heated to 42 degrees C. Plasma samples were collected before bathing, immediately after bathing, and 60 minutes after bathing. The scores were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Other research is looking at the effects of the presence of water because a growing body of evidence suggests that time spent in or near natural water environments, such as the coast, rivers, lakes, and inland waterways, can promote health and well‐being (European Centre for Environment and Human Health, ). In other Japanese studies that used tactile experiences, positive effects were found: bathing in hot, deep seawater significantly reduced the lactate concentration in the participants 60 min after bathing (Tsuchiya et al , ) and floating in seawater decreased salivary chromogranin A, one of the stress markers (Motomura, Arakawa, Toyosato, & Yokota, ).…”
Section: Introductionmentioning
confidence: 95%
“…Other research is looking at the effects of the presence of water because a growing body of evidence suggests that time spent in or near natural water environments, such as the coast, rivers, lakes, and inland waterways, can promote health and well‐being (European Centre for Environment and Human Health, ). In other Japanese studies that used tactile experiences, positive effects were found: bathing in hot, deep seawater significantly reduced the lactate concentration in the participants 60 min after bathing (Tsuchiya et al , ) and floating in seawater decreased salivary chromogranin A, one of the stress markers (Motomura, Arakawa, Toyosato, & Yokota, ).…”
Section: Introductionmentioning
confidence: 95%
“…As we know, seawater has been used in the therapy for atopic dermatitis for a long time. Recently, DSW has been also used for thalassotherapy (Tsuchiya et al. 2003a,b, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also, among JSPW, SSW, and PW, JSPW was shown to be mildest to the human body (7). In addition, subjects reported a sticky feeling after SSW bathing, whereas no sticky feeling was reported after JSPW bathing (6,7).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies regarding the effects of balneotherapy in the treatment of some diseases at the Dead Sea have been published (2)(3)(4)(5). Furthermore, we previously demonstrated that hot JSPW bathing had a beneficial influence on human health (6,7). Therefore, it is expected that use of JSPW will be promoted for human health.…”
Section: Introductionmentioning
confidence: 97%